Intercultural competence in multimodal reading comprehension: content validation of a didactic proposal for a multicultural classroom - Mardones, Tricia; Sotomayor, Carmen; Escobar, Diego (Frontiers in Education, 2024)
Globally, school classrooms are becoming more and more multicultural, since migration is a phenomenon that has an impact on a planetary level. In Latin America and the Caribbean, different migration flows have occurred in the last 10 years, as a result of natural disasters, political instability, and the search for optimal wages, among other reasons. The migrant population carries with them their cultural identity, which is reflected in the classroom. In the Chilean case, there are schools with a high percentage of Latin American migrant students, which implies an intercultural pedagogical challenge. In the context of learning reading comprehension, data emerge that place migrant students on the SIMCE Reading test with lower scores than local students. Reading performance may have causes in the access gap as an educational level. However, despite the origins of this inequality, there is an immediate need to intervene didactically in the classroom to enhance reading comprehension in multicultural contexts. The preliminary results of a larger research that had as one of its objectives to design and validate the content of a didactic proposal to enhance multimodal reading comprehension by integrating intercultural competence in school contexts with the integration of migrant students are reported. This study uses the quantitative method with a non-experimental and cross-sectional design. Twelve class sessions were designed with their didactic material. Fifteen expert judges validated the proposal. The instrument used was a validation guideline built ad hoc for the research. For the analysis, the agreement of the judges was calculated using the relevance index, Aiken’s V and Lawshe’s content validity ratio. It was possible to obtain a coherent and consistent didactic proposal, which would allow it to be implemented in multicultural school contexts. A didactic proposal is obtained that addresses both the guidelines of intercultural competence and the didactics of language for the understanding of multimodal genres, considering the cultural identity of the students. It is considered that both perspectives in multicultural contexts can be approached at the same time without losing the development of understanding.